2006
DOI: 10.1136/jcp.2005.033746
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein isoform II expression in hyperplastic, dysplastic and neoplastic prostatic lesions

Abstract: Background: Metallothionein is a low-molecular-weight cysteine-rich protein that has the ability to bind and sequestrate heavy metal ions. It is associated with metalloregulatory functions such as cell proliferation, growth and differentiation. Aims: To investigate the expression of metallothionein in hyperplastic, dysplastic and neoplastic prostatic lesions and to correlate its expression with histological grade of prostatic carcinoma. Method: The study was carried out on formalin-fixed and paraffin-wax-embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Four studies were included in total [67], [121][123]. Athanassiadou and Moussa used Gleason scale as a measure of tumor grading.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were included in total [67], [121][123]. Athanassiadou and Moussa used Gleason scale as a measure of tumor grading.…”
Section: Resultsmentioning
confidence: 99%
“…At the present time, only few studies provided limited information of MT1/2 expression in human prostate tissues. Among these data, the correlation of the positive IHC staining of MT1/2 and the adenocarcinoma status was variable ranging from 33% (15/45) [ 30 ], 67% (20/30) [ 31 ] to 100% (5/5) [ 32 ]; while some reports indicated that the Gleason grades of the tumor tissue scoring from low to high reversely corresponded to the intensity of MT1/2 IHC staining [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…MT can also serve as a serum tumor marker in prostate cancer Masarik et al, 2011), head and neck tumors , childhood solid tumors , and melanoma . Expression of MT may help to distinguish between benign and malignant tumor, as shown in thyroid tumors (Krolicka et al, 2010), prostatic lesions (El Sharkawy et al, 2006), GI stromal tumors, and gastric carcinomas (Soo et al, 2011). At isoform levels, MT expression in breast and prostate cancers, renal tumors, and papillary thyroid cancer was reviewed by Thirumoorthy et al, who found that expression of MT Drug Metabolism Reviews Downloaded from informahealthcare.com by University of Sussex Library on 10/17/12…”
Section: Mts In Cancer Diagnosismentioning
confidence: 99%